THE EFFECT OF PARTNER READING STRATEGY ON THE STUDENTS' READING COMPREHENSION AT MAS PAB 1 SAMPALI - Shooziki, Muhammad (Faculty of Tarbiyah nad Teacher Training, 2024)
Reading comprehension requires greater concentration than other English language skills. This is why reading comprehension is difficult to learn or teach. However, there is one learning strategy called partner reading strategy. The purpose of this study was to find out the effect of reading partner strategy on students’ reading comprehension. This study used a quantitative research method with a quasi-experimental design. This study was conducted at MAS PAB 1 Sampali, with a population of all tenth grade students from two classes. The research sample consisted of 26 students in class X-1 as the control class and 21 students in class X-2 as the experimental class. This study was carried out through three stages, namely pre-test, treatment, post-test. Each sample went through the same stages, but the control class was given a conventional teaching strategy while the experimental class was given a partner reading strategy. The results showed that the mean scores of the post-test in both classes were far different. In the control class, the mean score was 72.62; while in the experimental class was 84.19. Furthermore, the independent sample t test result showed that the Sig. 2-tailed was 0.000, where it was smaller than 0.05 (0.000<0.05). In conclusion, Ha is accepted and H0 is rejected.